Study on Characteristics of Coupled-Core Four-Core Fibers With Different Core Pitches - Junjie Xiong; Lin Ma; Yanming Chang; Tianqi Cheng; Lei Shen; Lei Zhang; Changkun Yan; Lin Sun; Qingwen Liu; Zuyuan He (IEEE Photonics Journal)
We studied the characteristics of coupled-core four-core fibers (CC-4CFs) with different core pitches both theoretically and experimentally. The spatial mode dispersions of different fibers were analyzed, and the result agrees well with theoretical ones. In the experiment, we achieved a spatial mode dispersion as low as 3.72 ps/km1/2 for a 4 km-long CC-4CF with core pitch of 19 μm at a bending radius of 8 cm. The impulse response matrices of four core fibers with different core pitches was investigated using swept-wavelength interferometry over 100 nm bandwidth. The impulse responses were Gaussian-shaped and consistent between different inputs and outputs for CC-4CFs. Our results show that the CC-4CFs with core pitches of 17 and 19 μm exhibit narrower pulse broadening. In addition, the mode-dependent losses of different fibers were analyzed. For the fibers with core pitch of 19 μm, the estimated mode-dependent loss was lower than 3 dB for the entire 100 nm bandwidth. Our results are especially helpful for developing coupled-core multicore fibers for long-haul transmission applications.